Design and Implementation of Keyless Entry and Starter Rfid System on Daihatsu Xenia Type Xi Year 2010 - Bahtiar Wilantara; Sidik Purnomo; Ismail Kholid; Azka Relief F W (Politeknik Piksi Ganesha Indonesia, 2024)
The design and implementation of keyless entry and starter rfid on Daihatsu Xenia Type Xi Year 2010 aims to: 1) Know the tools and materials used in the design and implementation of keyless entry and starter rfid on Daihatsu Xenia type Xi year 2010; 2) Understand the steps of the design and implementation of keyless entry and starter rfid on Daihatsu Xenia type Xi year 2010; 3) Be able to find out the results of testing the design and implementation of keyless entry and starter rfid on Daihatsu Xenia type Xi year 2010. The research method used is research and development. The steps of making the design include: The process of assembling an Arduino Uno-based rfid system, the process of inputting rfid tag data to the Arduino Uno, the process of assembling the keyless entry module cable to the car's electrical system, combining the keyless entry module with the Arduino Uno-based rfid system, placing the keyless entry module and the rfid system, finishing. Design and implementation of keyless entry and starter rfid on the 2010 Daihatsu Xenia Type Xi as a security feature on the 2010 Daihatsu Xenia Type Xi car. Based on the test results, it can be concluded that the design and implementation of keyless entry and starter rfid can work well, according to the following: increasing security, increasing comfort, increasing prestige, facilitating access, damage to the electrical system, not easily duplicated, still vulnerable to theft, easy battery drop, susceptible to electromagnetic signal interference.